Perceived Service Quality and Student Loyalty in an Online University - Martínez-Argüelles, María-Jesús; Batalla-Busquets, Josep-Maria (International Review of Research in Open and Distributed Learning, 2016)
This paper examines the influence that student perceived quality of service (PSQ) has on continuance intention and willingness to recommend a course in a fully online university. A holistic view of the service provided by the university is taken. It is not only the effect of the teaching which is examined, but also that of the administrative services, the additional services, and the virtual learning environment (user interface). Through a survey completed by 1,870 students and the subsequent analysis using structural equations, we found that each of these services has a significant impact on the students' PSQ, their level of satisfaction, and, as a result, their loyalty and willingness to recommend the university. The study found that the perceived quality of the administrative services can have a comparatively higher impact on student satisfaction than the other services. PSQ is shown to have also a direct impact on student loyalty and recommendations. Moreover, as a whole, non-teaching services have a greater impact on loyalty and willingness to recommend than teaching service. The peculiarities of the process of providing educational services in a virtual environment (such as the absence of face-to-face interaction between student and teacher and the lack of conventional tangible elements which act as benchmarks for quality of service) are well-known. The relationship established in the literature between the constructs of service quality, satisfaction, loyalty, and willingness to recommend the service in an offline environment can also be seen in this context. The interconnection of factors proves to be more complex and interrelated than has been accounted for as yet in the scholarly literature. The findings of the survey are relevant to system concerns related to quality management and sustainability, both of which are increasingly important in today’s competitive educational postsecondary environment.